Tolerability, safety and survival in patients with severe pulmonary arterial hypertension treated with intravenous epoprostenol (Veletri®): a prospective, 6-months, open label, observational, non-interventional study - Degering, Julia; Egenlauf, Benjamin; Harutyunova, Satenik; Benjamin, Nicola; Salkić, Amina; Xanthouli, Panagiota; Eichstaedt, Christina; Seeger, Rebekka; Sitbon, Olivier; Grünig, Ekkehard (Respiratory research, 2023)
Background: Epoprostenol AS (Veletri®), a thermostable epoprostenol formulation, provides better drug stability and improved clinical use compared to previous epoprostenol formulations. This study aims to expand clinical experience in the use of Veletri®, especially regarding tolerability, safety and survival. Methods: Pulmonary arterial hypertension (PAH) patients at high risk despite pretreatment with at least double oral combination therapy and with clinical indication for epoprostenol (Veletri®) treatment were consecutively included in this prospective, open label, observational, non-interventional study. Clinical data were assessed at baseline, after 3 and 6 months. Adverse events (AEs) and serious adverse events (SAEs) were documented. Survival from initiation of Veletri® was assessed at last patient out. Results: Fifteen patients (60 ± 13.7 years, WHO functional class III (n = 10) or IV (n = 5), severely impaired right ventricular function, mean pulmonary arterial pressure 54.8 ± 8.9 mmHg, mean pulmonary vascular resistance 4.4 ± 0.7 (median 3.8) Wood Units) were enrolled and treated with a mean dosage of 7.9 ± 3.9 (median 7.5) ng/kg/min. Eleven patients completed the study (treatment withdrawal n = 1, death n = 3). After a mean follow-up of 19.1 ± 13.5 (median 18.0) months, seven patients died and three were listed for lung transplantation. Seven AEs (nausea n = 3, diarrhea n = 1, flushing n = 2, headaches n = 1) and three SAEs (catheter infection n = 2, catheter occlusion n = 1) were related to Veletri®. The 1- and 2-year survival rates were 73.3% and 52.4%, respectively. Conclusions: The study showed that safety and tolerability of epoprostenol AS (Veletri®) was comparable to previous prostacyclin formulations and was feasible for most patients. The maximum tolerable dosage was lower than dosages reported in the literature. In future applications/trials the up-titration process should be pushing for higher dosages of epoprostenol in the occurrence of side effects, as the achievement of a high and effective dosage is crucial for the clinical benefit of the patients. Survival was as expected in these prevalent severely impaired patients. Trial registration The study was registered in the EUPAS registry (EUPAS32492).
Gesehen am 30.03.2023